Tax planning and shareholder wealth maximization among listed banks in Nigeria - Efenyumi, Peter-Mario Efesiri; Nworie, Gilbert Ogechukwu (Goodwood Publishing, 2025)
Purpose: This study examines the nexus between tax planning and shareholder wealth maximization among listed banks in Nigeria. The specific objective was to estimate the extent to which the effective tax rate affects the total shareholder return. Method: An ex-post facto research design was adopted on a population of 12 listed deposit money banks in Nigeria. Purposive sampling was used to select a sample size of nine banks. Secondary data for the study were sourced from the annual reports of banks from 2014 to 2023. Cross-sectional, seemingly unrelated regression was carried out to test this hypothesis. Results: It was found that a reduction in the effective tax rate will increase the total shareholder return of listed banks in Nigeria (? = -0.171827, p = 0.0000). Conclusions: Tax planning enables companies to strategically manage their tax liabilities by minimizing tax expenses by taking advantage of available deductions, credits, and exemptions. As per policy implications, Nigerian tax authorities should continuously assess tax liabilities and implement legal tax minimization strategies. Limitations: This study is limited by its focus on listed deposit money banks in Nigeria, which restricts the generalizability of the findings to other financial institutions. Contribution: This study contributes to the literature by filling a critical gap by focusing on sector-specific profitability metrics, as it offers a new perspective on the liquidity-performance relationship in Nigerian agricultural firms.